(untitled) (Comparative & International Education Series, 2021)
Foreign-born faculty enrich the fabric of the United States educational system in numerous ways. Their diverse perspectives enhance the cultural landscape of departments and student learning. However, Foreign-born faculty face many issues and concerns that could have dire effects both professionally and personally, if under- or un-resolved. This chapter highlights the professional issues and concerns of Foreign-born faculty, the impact on their personal and professional lives, and strategies for successful outcomes. The intent is to facilitate a deeper understanding of the challenges of Foreign-born faculty, to promote personal wellness, and to advocate for supportive and inclusive institutional policies.